Implementasi sistem enterprise resource planning (ERP) berbasis odoo modul purchase pada PT X - Khairunisa Maharsanti (Qualitative Research of Business and Social Sciences, 2023)
The rapid development of technology has become the primary driver of change in the business world. Business processes previously carried out manually have now been replaced by machine technology that is more effective, efficient, and reduces human error. One of the systems or technologies used in this research is the Enterprise Resource Planning (ERP) system, which uses Odoo software and focuses on the purchasing module. The purpose of this research is to analyze strategies to overcome the problems of automation of the purchasing system, which is still done manually at PT X. This research uses a qualitative method with a case study approach at PT X. This retail company offers leading furniture products by providing the best quality furniture choices. This research also uses interview techniques and direct monitoring to observe changes in PT X operational business processes. The results of the interview with the mentor as the Founder & CEO of PT Ctech ERP Indonesia became the primary source of information regarding the implementation of the Odoo-based ERP version 16. The study results showed differences in PT X business processes, especially in the purchasing system before and after implementing the Odoo-based ERP system. After implementing the Odoo ERP system in the purchasing module, the effectiveness and efficiency of purchasing system management increased, which had a major impact on the company.